Anti-obesity drug discovery and development . - Rahman, Atta-ur-; Choudhary, M. Iqbal (Bentham Books, 2014)
Obesity is a complex health problem, caused by a number of factors such as excessive food intake, lack of physical activity, genetic predisposition, endocrine disorders, medications and psychiatric illnesses. Onset of obesity in both the developing and the developed world has reached epidemic proportions. In response to this, efforts to control and treat obesity have also been vigorously pursued, ranging from raising awareness about lifestyle changes to the discovery and development of safe and effective anti-obesity drugs. Anti-obesity Drug Discovery and Development is focused on this very imp.